ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM DI KABUPATEN TABANAN - ARTINI, NI RAI (GANEC SWARA, 2019)
This study aims to determine the effect of variables of capital and labor on MSME income in Tabanan Regency. This study uses 95 respondents spread across 10 Districts of Tabanan Regency, then the data are analyzed using multiple linear regression.     The results of the analysis simultaneously show that the variables of capital and labor have a significant effect on MSME income in Tabanan Regency. While the results of the partial analysis of the variables of capital and labor have a real influence on the income of MSMEs in Tabanan Regency. Capital is the dominant variable that affects income, the higher the capital will increase the amount of additional production so as to increase income. Likewise with labor, the more labor, the production will also increase